Diagnostic utility of translabial ultrasound in pelvic organ prolapse: a prospective observational study - Milosz Pietrus; Kazimierz Pityński; Iwona Gawron; Maciej W. Socha; Krzysztof Nowosielski; Robert Biskupski-Brawura-Samaha; Marcin Waligóra (Journal of Obstetrics and Gynaecology)
Background The increasing awareness of women’s health issues, specifically pelvic organ prolapse (POP) and urinary incontinence (UI), has spurred a surge in patients seeking specialised advice for these conditions, necessitating modern diagnostic approaches for such issues. This study explored the diagnostic utility of translabial ultrasound for POP, emphasising its correlation with clinical assessments based on International Continence Society (ICS) criteria.Methods Seventy-one patients with POP Quantification System (POP-Q) stage 0-IV with or without UI were prospectively enrolled at Jagiellonian University Medical College between 2014 and 2016. The study objectives included evaluating diagnostic accuracy and concordance across pelvic compartments, correlating the diagnoses with patient-reported symptoms, and identifying variables contributing to diagnostic discrepancies.Results Translabial ultrasound identified POP in 74.5% of the patients, aligning closely with clinical evaluations. Concordance was the highest in assessments performed in the medial compartment (85.8%), while assessments performed in the anterior (29.6%) and posterior (29.6%) compartments showed higher rates of discrepancies. Correlation analyses showed varying associations, with the posterior compartment exhibiting the least pronounced correlation (R = 0.72, p < 0.0001). Self-perceive POP showed no discernible differences in relation to ultrasonographic and clinical assessments. Among the respondents, 55.9% reported experiencing the sensation of POP. Mean POP levels determined using the two approaches precisely matched in 46.5% of these cases. Discrepancies involved variables such as self-perceived POP, number of deliveries, child weight at birth, UI, and sexual activity.Conclusions Translabial ultrasound showed robust correlation with clinical assessments for evaluating POP, especially for defining defects and facilitating treatment-related decision-making. Our findings highlight the reliability of this method, particularly for assessments in the medial compartment. The evidence did not indicate the superiority of either method in detecting POP disorders for symptomatic versus asymptomatic patients. Significantly, a higher POP-Q measurement in clinical examination was correlated with greater sexual activity.